La lectoescritura y su incidencia en el proceso de enseñanza- aprendizaje en el cuarto grado de educación básica de la Unidad Educativa Adolfo María Astudillo del Cantón Babahoyo, Provincia de Los Ríos - Zambrano Monserrate, Sandy Marisela (2020)
Literacy is the fundamental skill for the development of the human being, it is for this reason that this study of cas is important because it seeks to be aware of how literacy affects the teaching-learning process. of students, therefore, has as main objective to analyze the impact of literacy in the teaching-learning process for the students of the Adolfo María Astudillo Educational Unit of the Babahoyo Canton, Province of Los Ríos. This work was carried out thanks to the knowledge and application of exploratory, documentary and explanatory, quantitative and qualitative research, which was intended for a number of students in this case in the fourth year. The teachers of the establishment, thanks to the survey conducted with this source, verified the hypothesis, which with an established formula was accepted, whose theme is Literacy and its impact on the teaching-learning process in the fourth grade of basic education of the Unit Educational Adolfo María Astudillo of Canton Babahoyo, Province of Los Ríos, which led to the conclusion that literacy is important in the life of each student because it is the principle of internalizing knowledge, thus recommending that teachers apply strategies, techniques based on the needs observed in class that point to an easy understanding of what has been read and the correct development of writing.